Reaction of Pyridoxal with Phenols: Synthesis of Novel 1-Aryl-Substituted Furopyridines - Kibardina, Ludmila K.; Chumakova, Ludmila V.; Gazizov, Almir S.; Burilov, Alexander R.; Pudovik, Michail A. (Synthesis, 2015)
A new method based on the acid-catalyzed reaction of pyridoxal with polyfunctional phenols has been developed for the synthesis of potentially biologically active 1-aryl-6-methyl-1,3-dihydrofuro[3,4-c]pyridin-7-ols. Advantages of this method include a good yield of the target furopyridines and the use of readily available hydrochloric acid as a catalyst. The possibility of extending the proposed approach to nucleophiles other than phenols was demonstrated by the synthesis of the known biologically active compound 1-(5-hydroxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)-6-methyl-1,3-dihydrofuro[3,4-c]pyridin-7-ol hydrochloride (TM2002).
Keywords: phenols; furans; pyridines; aldehydes; polycycles; heterocycles